Children with burns referred for child abuse evaluation: Burn characteristics and co-existent injuries. (May 2016) - Pawlik, Marie-Christin; Kemp, Alison; Maguire, Sabine; Nuttall, Diane; Feldman, Kenneth W.; Lindberg, Daniel M.; ,
Abstract: Intentional burns represent a serious form of physical abuse that must be identified to protect children from further harm. This study is a retrospectively planned secondary analysis of the Examining Siblings To Recognize Abuse (ExSTRA) network data. Our objective was to describe the characteristics of burns injuries in children referred to Child Abuse Pediatricians (CAPs) in relation to the perceived likelihood of abuse. We furthermore compare the extent of diagnostic investigations undertaken in children referred to CAPs for burn injuries with those referred for other reasons. Within this dataset, 7% (215/2890) of children had burns. Children with burns were older than children with other injuries (median age 20 months vs. 10 months). Physical abuse was perceived as likely in 40.9% (88) and unlikely in 59.1% (127). Scalds accounted for 52.6% (113) and contact burns for 27.6% (60). Several characteristics of the history and burn injury were associated with a significantly higher perceived likelihood of abuse, including children with reported inflicted injury, absent or inadequate explanation, hot water as agent, immersion scald, a bilateral/symmetric burn pattern, total body surface area ≥10%, full thickness burns, and co-existent injuries. The rates of diagnostic testing were significantly lower in children with burns than other injuries, yet the yield of skeletal survey and hepatic transaminases testing were comparable between the two groups. This would imply that children referred to CAPs for burns warrant the same level of comprehensive investigations as those referred for other reasons.